Scanning Probe Microscopy Bone Marrow Determination of Steogenic Differentiation of Mesenchymal Stem Cells. (8th July 2022) - Fu, Xiandong; Lian, Qixin; Zhang, Bo; Teng, Xinli; Chen, Ying; Qu, Yikun; Cheng, Zhuoxin; Guo, Linqi
Abstract : To address the question of determining the osteogenic differentiation of mesenchymal stem cells, the bone marrow studies were performed using probe microscopy. All adherent bone marrow was used to isolate the bone marrow mesenchymal stem cells and expanded and purified in vitro. Its morphology under an inverted microscope was observed. We used Zuogui Pills to differentiate the separation methods. Alcian blue staining, modified calcium cobalt alkaline phosphatase staining, and neuron-specific enolase immunohistochemical staining were performed. The experimental results are shown below. The morphology of the isolated and purified cells was analyzed with an inverted microscope, and the isolated and purified cells were analyzed with Zuogui Pill. Alcian blue staining, modified calcium cobalt alkaline phosphatase staining, and neuron-specific enolase immunohistochemical staining confirmed that the cells differentiated into cartilage and osteoblasts, and the cell structure and morphology were similar to those of the bone marrow mesenchymal stem cells. The results showed that the adherent mode of cells obtained from the whole bone marrow was the rat bone marrow mesenchymal stem cells, and the Zuogui Pills could induce multidirectional differences in the bone marrow mesenchymal stem cells.